2017
DOI: 10.1080/15298868.2017.1371636
|View full text |Cite
|
Sign up to set email alerts
|

“Behave like a responsible adult” – Relation between social identity and psychosocial skills at stake in self-management of a chronic disease

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…As duas pesquisas anteriores concluíram sobre a necessidade de melhor levar em conta os aspectos psicossociais do autocuidado nos programas de educação terapêutica. Para responder a esse desafio, uma terceira pesquisa foi realizada com o objetivo de explorar as expectativas e necessidades de cada um dos atores na situação terapêutica Apostolidis, 2018). Essa exploração foi realizada utilizando dez grupos focais constituídos por adolescentes com diabetes, seus pais e profissionais de saúde.…”
Section: Tabela 1 -Síntese Dos Objetivos Métodos E Resultados De Cadunclassified
“…As duas pesquisas anteriores concluíram sobre a necessidade de melhor levar em conta os aspectos psicossociais do autocuidado nos programas de educação terapêutica. Para responder a esse desafio, uma terceira pesquisa foi realizada com o objetivo de explorar as expectativas e necessidades de cada um dos atores na situação terapêutica Apostolidis, 2018). Essa exploração foi realizada utilizando dez grupos focais constituídos por adolescentes com diabetes, seus pais e profissionais de saúde.…”
Section: Tabela 1 -Síntese Dos Objetivos Métodos E Resultados De Cadunclassified
“…Specifically, the archetype of the reckless adolescent would only make sense in a relation of opposition to the archetype of the autonomous and responsible adult as can be promoted in the ideological context of Western liberal societies (Arnett, 2006). This opposition is interesting to point out, since it has been shown that the adoption of diabetes self-management behaviours is associated with the acquisition of an adult identity in the neoliberal context (Fonte et al, 2018). Thus, in the context of therapeutic education, professionals and parents are always likely to maintain a climate of distrust towards adolescents with diabetes because they would presume an adherence on their part to values that are at odds with those of the adult world.…”
Section: Discussionmentioning
confidence: 99%
“…In self-management as commonly 'done', the patient is expected to take responsibility for their condition. Fonte and colleagues 20 argue that although the process of assuming responsibility is a key self-management skill, the literature has tended to ignore the psychosocial processes that are involved with taking on this responsibility. In their paper, they frame the process of taking responsibility as presenting oneself as an adult.…”
Section: So Where Does 'Life-context' Fit?mentioning
confidence: 99%